Implementation of Makassar City Coastal Area Protected Area Policy - kadir s, abd; Madani, Muhlis; Burhanuddin; Fatmawati, Fatmawati; Parawu, Hafiz Elfiansya (Universitas Medan Area, 2024)
Coastal areas are dynamic areas with interactions between land and sea, which exposes complex challenges in integrated management. Law No. 1 of 2014 on the management of coastal areas and small islands in Indonesia is a step to increase state authority in coastal waters management. However, environmental sustainability is often not a top priority in practice. This condition is reflected in various phenomena in Makassar City, where development and human activities have resulted in damage to the coastal environment and marine pollution. This study uses a qualitative approach to analyze the implementation of coastal protection policies in Makassar City. Through interviews with various stakeholders, including government agencies, NGOs, and communities, it was found that there are still many as challenges faced in implementing this policy. Among them are the readiness of human resources in various relevant agencies, effective communication between parties, complex bureaucratic structures, and the important role of the private sector. With cooperation and commitment from all parties, it is hoped that the implementation of coastal area protection policies can be successful and have a positive impact on the environment and coastal communities of Makassar City.